Effect of Conjugated Linoleic Acid (CLA) Supplementation on Dry Matter intake, Metabolisable Energy intake and changes in Bodyweight of Crossbred Cows during Transition Period - J.S. Sidhu; R. S. Grewal; J.S. Lamba; Chanchal Singh; A.P.S. Sethi (Indian Journal of Animal Nutrition, 2023)
The effect of CLA supplementation on dry matter intake (DMI), metabolisable energy intake (MEIntake) and bodyweight was studied in cross bred cows during the transition period. Thirty multiparous crossbred cows (n=30) were split into three groups and fed one of the following three experimental diets: 50 g of bypass fat was added as a supplement to the T1 group's basal diet, 25 g of CLA and 25 g of bypass fat were added to the T2 group's diet, and 50 g of CLA was added to the T3 group's diet. Beginning 21 days after calving, supplementation continues until 60 days in milk (DIM). The basal diet was same in all the experimental groups. Samples of the feed and residue were examined for chemical makeup. The ME values of the ration were determined using the invitro gas fermentation technique on feed samples. Body weightof cows was recorded at 14-dayintervals before the morning feeding and on error-free weighing balance.DMI, ME, and nutritional intake were comparable among groups, indicating that supplementation had no significant impact. Moreover, the loss/changes of body weight in the animals during the transition period was similar between the different experimental groups suggesting the similar efficacy of bypass fat and CLA in countering negative energy balance and improving the animals' body condition scores as the animals continued to gain weight in the postpartum period.